COVID‐19 and Postgraduate Dental Training—A commentary. (29th September 2020) - Mahendran, Krishantini; Yogarajah, Sangeetha; Herbert, Cameron; Nayee, Shalini; Ormond, Martyn
Abstract: In this commentary, we discuss the short‐term and long‐term implications of COVID‐19 on postgraduate dental training in the UK, specifically Dental Core Training (DCT) and Specialty Training. Although this commentary focuses on the authors' experiences within Guy's and St Thomas' NHS Foundation Trust (GSTT) in London, we hope that our viewpoint will resonate with dental postgraduate trainees across Europe and may guide further discussion in this area. We also reflect on adaptations that may be required if there are any future disruptions to dental postgraduate training in the UK.